Students’ Perceptions on the Use of English as Medium of Instruction (EMI) at The International Class of The Economic Development Study Program of The Faculty of Economic & Business of University of Bengkulu - Muhammad Rafiq Tanjung; Azwandi Azwandi; Sufiyandi Sufiyandi (Universitas Bengkulu, 2021)
The objective of this research is to investigate the students’ perceptions on the use of English as a Medium of Instruction (EMI) at the International Class of Economic Development Study Program Faculty of Economics and Business of University of Bengkulu. This research used descriptive quantitative survey design. Questionnaire and interview were the instrument of the research. The questionnaire was distributed to all population of this research, which was 19 students. The sample of the interview was 5 students. The result of this research showed that most of the respondents were positive with the statements given. In perceiver dimension, positive responses were the highest consisting of 37.9% of students agreed and 26.3% of students strongly agreed. In target dimension, positive responses were the highest consisting of 48.1% of students agreed and 32.3% of students strongly agreed. Meanwhile, in situation dimension positive responses were also the highest percentage consisting of 44.7% of students agreed and 9.2% of students strongly agreed. In conclusion, the majority of the students are positive with the EMI program in their class either in terms of perceiver, target, and situation. However, more than half of the students were not confident in terms of communicating with English in learning process. Besides, the implementation was still partial in most courses.